Active smoking and second-hand-smoke exposure at home among Irish children, 1995–2007. Issue 1 (19th October 2009) - Kabir, Z; Manning, P J; Holohan, J; Goodman, P G; Clancy, L
Abstract : Objective: This study hypothesised a continual decline in current smoking prevalence over four calendar years (1995, 1998, 2002/03 and 2007) and no significant increase in second-hand-smoke (SHS) exposure levels at home after the workplace smoking ban of March 2004 (2007 versus 2002/03 survey) among Irish school children. Methods: A modified ISAAC (International Study of Asthma and Allergies in Childhood) protocol was used. Children aged 13–14 years from randomly selected representative post-primary schools were studied: 2670 in 1995, 2273 in 1998, 2892 in 2002–2003, and 2805 in 2007. ISAAC is a cross-sectional self-administered questionnaire survey. Smoking history was self-reported. β Coefficients (slopes) of smoking rates across the four surveys were computed. Odds ratios for smoking rates were also computed using the baseline year (1995) as the reference period. All analyses were performed using SAS software (v 9.1). Results: There were significant reductions in active smoking rates between 1995 and 2007 (from 19.9% to 10.6%, respectively) resulting in 3.3% survey-to-survey reductions, with a significantly greater survey-to-survey decline among girls compared to boys (3.8% vs 2.7%, respectively). 45% of children were exposed to SHS at home in 2007. There was a statistically non-significant 2% overall decline in SHS exposure levels at home in 2007 relative to 2002/03, which was more pronounced in girls. Conclusions: The continual reduction in active smoking prevalence in children is welcome. That there was no significant increase in SHS exposure at home after the nationwide workplace smoking ban suggests that the ban did not increase smoking inside homes.